Patterns, Associated Factors, and Clinical Outcomes of Poisoning among Poisoning Cases Presented to Selected Hospitals in Western Ethiopia: Hospital-Based Study - Ashenafi Habte Woyessa; Thanasekaran Palanichamy (Emergency Medicine International)
Back Ground. Epidemiological data related to poisoning is very limited in Ethiopia. Therefore, this study was carried out to assess the patterns, associated factors, and clinical outcomes of poisoning among poisoned cases brought to selected hospitals in western Ethiopia. Methodology. Hospital-based prospective cross-sectional study design was employed. Five administrative zones in west Ethiopia were selected as geographical clusters. Area sampling technique was utilized to select the hospitals. Finally, consecutive sampling technique was used to recruit the study participants. Since the objective of this study was to determine the pattern and outcome of poisoning during the specified study period, no specific sampling size determination was employed. As such, all of the 211 poisoned cases presented to the selected hospitals during the specific study period were consecutively included. Data were collected using a comprehensively organized and pretested interviewer-administered questionnaire. Results. The broad types of poisoning were identified in about 193 (91.47%) cases of poisoning in this study. Pesticides exposure and food poisoning have, respectively, contributed for 32.70% and 20.91% of the poisoning incidence. On the other hand, chemical from industry has contributed the least percentage (2.81%). Out of a total of 24 agents identified, 26.80% of the agents were organophosphates followed by raw meat (18.40%). Difference in the incidence of poisoning was also observed as seasons in a year change. Among the victims who have taken household materials as a poisoning agent, about 47.87% of them have taken the agents during daytime. The remaining cases of poisoning developed by household chemicals occurred at night. More than half (54.98%) of the poisoned patients have encountered the incidents inside their home. Regarding the final poisoning outcome, about 7.10% poisoning cases in this study died of the poisonings. Factors such as place, time, intention, and source of poisoning were observed to determine poisoning outcomes. Although poisoning attempt was lesser among urban residents as compared to rural community, rural dwellers were four times more likely to die of poisoning they had attempted (AOR: 4.072 (1.197–13.85)). Conclusion. This study has clearly showed that the incidence of poisoning was varied with seasonal variations. The encountered poisonings ended up with mixed clinical outcomes, which were also affected by patients’ demographic and clinical characteristics. Fertilizers, unclean food items, household materials, and drugs have caused majority of the poisonings. Creating community awareness and designing sound prevention strategies are recommended to reduce morbidity and mortality related to poisoning.